Hypopharyngeal carcinoma in Finland from 2005 to 2014: outcome remains poor after major changes in treatment - Keski-Säntti Harri; Luukkaa Marjaana; Carpén Timo; Jouppila-Mättö Anna; Lehtiö Kaisa; Mäenpää Hanna; Vuolukka Kristiina; Vahlberg Tero; Mäkitie Antti (SPRINGER, 2022)
Purpose
Hypopharyngeal carcinoma (HPC) is typically diagnosed at late stages, the patients tend to have serious co-morbidities, distant relapses are frequent, and the related mortality remains high. The treatment paradigm of HPC has remarkably changed from primary surgical approach toward definitive, platinum-based concomitant chemoradiotherapy (CRT). Our aim was to analyze the HPC treatment approaches and outcome in a nationwide series and to make a comparison with a previously published corresponding nationwide patient cohort from the period 1990-1999.
Methods
We retrospectively reviewed all patients diagnosed with HPC at the five university hospitals in Finland between 2005 and 2014.
Results
The cohort comprised 231 patients. Treatment with curative intent was offered for 175 (76%) patients and consisted of definitive radiotherapy (RT) or CRT in 156 (89%) patients, while 20 (11%) patients had primary surgery with or without adjuvant RT or CRT. The 5-year estimates for overall survival (OS) and disease specific survival (DSS) for the whole study group were 22.7% and 36.5%, respectively. For patients treated with curative intent, the 5-year estimates for OS and DSS were 29.4% and 44.3%, respectively.
Conclusions
The treatment approach of HPC in Finland has changed thoroughly, as in the 1990s, 63% of HPC patients with curative treatment intent underwent primary surgery with or without RT, while in the current study, the primary treatment approach was non-surgical in 89% of the patients. However, the survival figures have not changed and remain dismal, but most of the few surviving patients now can retain their larynx.